儒家的“生生”理念及其衍生的生命倫理原則: The "Life" Idea of Confucianism and Its Derivable Bioethical Principles - YANG, Tongwei; WANG, Yunling (International Journal of Chinese & Comparative Philosophy of Medicine, 2007)
LANGUAGE NOTE | Document text in Chinese; abstract also in English. “天地之大德曰生”這一命題是儒家生命哲學的集中體現。這裏的“天地”不僅是客觀的存在，還具有德性倫理的光輝﹔這裏的生命，同時也是人文的終極意義所在——使生命成為生命，使人與自然界相統一而共同歸宿於整個宇宙的精神生命、宇宙生命。 天以“生”為其大德，這說明天不僅具有生命意義，而且具有價值意義。生命遵循本體原則，生生不已，發用流行。由此可見，在儒家的“生生”理念中，內含著對“天命”與“理”的深深敬重：對生命起源的敬重、對天地間萬物的敬重、對天地人相通的敬重。在敬重原則的指引下，悲天憫人，珍重生命就成為儒家的重要思想。 儒家所言的生命，是指能夠自我發展、自我創造、自我演化、自我更新的存在物。所以在“生生”理念中內含著目的性：凡生命都是有目的性的，“生”的目的性是完善和完美。這樣，出於對生命的敬重和對生命目的性的認識，“生生”理念便衍生出“盡性”原則：萬物各盡其性分。盡興原則，在先秦儒家那裏體現為取之以度、用之以時的生態倫理思想。而後世儒家則進一步認為，在整個自然界和社會中任何一人任何一物均有其各自獨立的生命價值和生命意義，因此皆應予以尊重理解和愛護。 在儒家看來，認識的目的在於為其道德實踐服務。在道德實踐層面，“生生”表現為一種追求和諧的“生生”，即人要順從自然以達到天、地、人之間的和諧。生生和諧摒棄了人與自然的對立，是一種仁民愛物、萬物一體的內在人文主義思想。通過生生和諧，使自然、人類、社會成為一個系統的有機的整體。這既代表了人類肯定、培護、滋潤自我生命的需要，也代表了人類生存、發展的方向。 "The great virtue of Heaven and Earth is life" – this proposition is a concentrated expression of the Confucian philosophy of life. Here, "Heaven and Earth" is not just an objective existence, but also has the virtue that is ethically brilliant. That "life" is the great virtue of Heaven shows that Heaven not only has the meaning of life but also has the sense of value. Thus, the Confucian philosophy of life, which holds a deep respect for "fate", and "truth", respects the origin of life, respects everything between heaven and earth, and respects the link among heaven, earth and person. Under this principle of respect, cherishing life becomes an important Confucian thinking. The life that Confucian said is the existence that can have self-development, self-creation, self-evolution and self-renewal. Therefore, the "life" idea including the principle of purpose: every life is purposeful, the purpose of life is to improve and perfect. Due to the respect for life and the purpose of life, "life" idea leads to the "development" principle: all things are full with the development. Confucians in the Qin dynasty thought that the development principle implies an ecological ethics that is limited to the use of season. Later, the Confucian further thought that any one or any person has its own independent life value and meaning of life. So all things should be respected, understood and loved. From the Confucian view, the purpose of cognition is service to moral practice. On morally practical level, "life" involves a pursuit of harmony. People ought to attempt to attain the harmony among heaven, earth and the people. It is an inherent humanism thinking that love should go for all the people, with differentiation notwithstanding. Through harmony, natural, human and social systems will come as an organic whole. This not only represents the needs of humans to cultivate and nurture self-life, but also represents a developmental human direction. DOWNLOAD HISTORY | This article has been downloaded 28 times in Digital Commons before migrating into this platform.